Unravelling Transplant-Ineligible Newly Diagnosed Multiple Myeloma Treatment in Real-World Practice in Spain: The CARINAE Study - Felipe de Arriba de la Fuente; Mercedes Gironella Mesa; Miguel Teodoro Hernández García; Juan Alonso Soler Campos; Susana Herráez Rodríguez; María José Moreno Belmonte; Teresa Regueiro López; Miriam González-Pardo; María Casanova Espinosa; on behalf of the CARINAE Study Investigators (MDPI AG, 2024)
Real-world evidence on the impact of monoclonal antibodies as first-line treatment in Spain is limited. This observational, retrospective and prospective, multicenter, descriptive study included 117 transplant-ineligible newly diagnosed multiple myeloma (TIE-NDMM) patients divided into Group A, who received no daratumumab standard regimens, and the DVMP group (daratumumab, bortezomib, melphalan, and prednisone treatment). More than 90% of the patients in Group A received bortezomib, lenalidomide, or a combination of them. The median follow-up time for Group A was 38.2 months in comparison to 25.8 months for the DVMP group (p < 0.0001). The rate of DVMP patients that experienced disease progression or death from any cause was 36.8%, compared to 67.3% of Group A patients at 36 months of follow-up. The DVMP group had a higher 36-month progression-free survival (PFS) rate (52.9% vs. 31.7%). During the retrospective period, 73.0% of patients reported adverse drug reactions, while in the prospective period, 40.5% experienced adverse events, with no clinical differences between groups. The study supports the use of daratumumab regimens in frontline therapy based on real-world data. The findings provide valuable insights into the clinical outcomes of daratumumab therapy, which can help physicians make informed decisions regarding the optimal treatment approach for this patient population.